Could PES Change the Agrarian Structure? a Lesson Learned of Citaman Village, Banten - sarifuddin, Andri; Adiwibowo, Suryo; Mardiana, Rina (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2020)
This study aimed to analyze changes in the agrarian structure in Citaman Village, whether or not capitalists enters the formation of community land, after payment for Environmental Services (PES) mechanism is effective. This research relies on the constructivism paradigm, using qualitative method. The primary data was collected through in-depth interviews and focus groups discussion, with farmer groups, community leaders and related parties. Relevant secondary data was also collected. The results show that: First the PES program which has been running for more than 15 years, has not changed the agrarian structure significantly in Citaman Village. The agricultural land is still dominantly controlled and owned by Citaman Village residents. Second the changes that occurred as a PES program were found in the patterns of agricultural land use. Agricultural land that was originally used for upland rice cultivation or huma is now turned into an agroforestry area.